2021
DOI: 10.1177/03635465211047485
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Revision Rotator Cuff Repair: The Role of Previously Neglected Subscapularis Tears

Abstract: Background: Concomitant full-thickness tear of the subscapularis tendon is often neglected during primary posterosuperior rotator cuff repair, and its significance has not been investigated by any previous clinical study. Purpose: To investigate (1) the clinical and radiological outcomes of revision arthroscopic rotator cuff repair and (2) the number of neglected concomitant subscapularis full-thickness tears in the revision of posterosuperior rotator cuff retears and their structural integrity after repair. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Yoon TH et al found that SSC tendon tears combined with advanced fatty infiltration had a high retear rate of 78.6% despite clinical improvement through surgery [ 19 ]. Among arthroscopic revision rotator cuff repairs, 43.1% had neglected SSC tears, and fatty infiltration of these initially neglected SSC tendons showed further progression at the time of revision [ 20 ]. When the SSC tendon tears extended more than the upper 1/3 of the tendon, the failure rate of massive posterosuperior rotator cuff tear repair was significantly increased [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yoon TH et al found that SSC tendon tears combined with advanced fatty infiltration had a high retear rate of 78.6% despite clinical improvement through surgery [ 19 ]. Among arthroscopic revision rotator cuff repairs, 43.1% had neglected SSC tears, and fatty infiltration of these initially neglected SSC tendons showed further progression at the time of revision [ 20 ]. When the SSC tendon tears extended more than the upper 1/3 of the tendon, the failure rate of massive posterosuperior rotator cuff tear repair was significantly increased [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intratendinous tear has not been introduced in the current classiications of SSC lesions [1][2][3]. Incomplete visualisation could lead to failure to diagnose SSC tears and subsequently have negative impacts on outcomes after rotator cuf repair [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…2,10,15,16,20,35,37 To prevent missed partial subscapularis tears, careful preoperative evaluation by physical examination and imaging is essential. 58…”
mentioning
confidence: 99%
“…2,10,15,16,20,35,37 To prevent missed partial subscapularis tears, careful preoperative evaluation by physical examination and imaging is essential. 58 Several clinical tests have been described for the diagnosis of subscapularis tears, including the belly-press test, belly-off sign, internal rotational lag sign, Napoleon sign (modified belly-press test), liftoff test, bear-hug test, and scissor sign. 3,14,18,19,22,40,45,46 Among them, the belly-press test and bear-hug test have been reported to have good diagnostic accuracy for detecting upper one-third subscapularis tears.…”
mentioning
confidence: 99%